Spatial Linkages of The Agricultural Sector in North Maluku in Indonesia: An Interregional Input-Output (IRIO) Approach - Saban, Asrilis Boy; Sahara; Falatehan, A Faroby (Jurnal Manajemen dan Agribisnis, 2023)
The purpose of this study was to analyze the linkages between the agricultural sector and other sectors in North Maluku and the linkages between the North Maluku agricultural sector and other economic sectors in 33 provinces in Indonesia. The data used is the 2016 Indonesia Interregional Input-Output (IRIO) Table data. Linkage analysis, forward linkages effect ratio (IDP) and backward linkages effect ratio (IDK) analysis in the IRIO approach were used to answer the research objectives. The results of the analysis show the forward and backward linkages of the agricultural sector in North Maluku with the highest rank in the food crops and livestock subsector. The IDP and IDK results show that food crops and fisheries are stronger in encouraging the development of downstream industries, while livestock is stronger in encouraging the development of upstream industries in North Maluku. The North Maluku agricultural sector that has the highest total forward linkages between regions is the plantation subsector with North Sumatra Province. The highest total backward linkage is the crop subsector with East Kalimantan. The results of this study should have implications for the evaluation process, and policy formulation of the North Maluku Regional Government. Especially the development of the agricultural sector as an input and output provider aspect. The government is expected to focus on cooperation policies between regions related to trade and market expansion in the agricultural sector. Keywords: sectoral linkages, regional linkages, agricultural sector, Interregional Input-Output (IRIO)